Phases of treatment for alcoholic patients. - Neto, D; Pereira, M G (Acta Médica Portuguesa, 2001)
Alcoholism remains a controversial area, concerning both theoretical definitions and modalities of clinical intervention. In spite of this, and perhaps as a consequence, it stands as a huge public health problem, consuming a large amount of resources (and mental health services resources in particular). Some clinical issues in this area are reviewed, according to the authors’ personal experience. Data related to clinical work in an alcohology centre (South Regional Alcohology Centre-CRAS) are presented. Based in a previous model of Sequential Combined Treatment of Heroin Addicted Patients with Naltrexone and Family Therapy, the authors outline some basic principles of a similar intervention designed for alcoholic patients and their families, which includes, when possible, a family integrated with an individual approach, an emphasis on normativity, on firmness and on self help groups. They revise, on the light of these concepts, the chain of medical care to these kind of patients, outpatient and inpatient, and the role of the medical doctor, which must not be confounded with the family system.